Reference values of serum total IgE in Uppsala – comparison over four decades - Movérare, Robert; Persson, Eilif; Malinovschi, Andrei; Janson, Christer (Upsala journal of medical sciences, 2023)
Background: Total immunoglobulin E (IgE) analysis is a common tool in allergy diagnosis. Suggested reference values for IgE are divergent and sometimes based on outdated assay methods. We aimed to validate the published reference values (geometric mean [GM]: 13.2 kU/L, upper limit of normal [ULN], 114 kU/L) shown in an Uppsala cohort from 1974 using Phadebas IgE PRIST, and the suggested clinical threshold of 100 kU/L (Zetterström and Johansson 1981). Methods: Immunoglobulin E was measured in two Uppsala cohorts from 1997 (Blood bank) and 2011 to 2013 (the European community respiratory health survey part III [ECRHS III]) using ImmunoCAP™ Total IgE. For the reference value calculations, exclusion criteria were atopy (both cohorts), doctor’s diagnosis of asthma and self-reported allergy (hay fever, rhinitis, rash) (only ECRHS III). Upper limit of normal was defined as mean + 2 standard deviations (SD) calculated using log-transformed values and back-transformation of the ULN prior to presentation. Common imputation methods for results below the assay range were evaluated. Results: The average GM was 14.2 kU/L (Blood bank, n = 63; imputation method range: 16.9–17.4 kU/L; ECRHS III, n = 113: 10.7–11.6 kU/L) and the overall mean ULN was 118 kU/L (Blood bank: 113–130 kU/L; ECRHS III: 104–128 kU/L). The clinical sensitivity and specificity of the 100 kU/L IgE threshold were 37.8 and 94.3% for atopy, 34.9 and 89.5% for doctor’s diagnosis of asthma, and 24.5 and 97.3% for any self-reported allergy (ECRHS III). Conclusion: The calculated ULN values were similar between the cohorts. We conclude that the total IgE reference values shown for Uppsala subjects from 1974 are still valid and suitable also for the ImmunoCAP Total IgE assay. The 100 kU/L threshold for total IgE had a low sensitivity but high specificity for atopy, asthma, and allergy.